Emerging trends in multiscale modeling of vascular pathophysiology: Organon-a-chip and 3D Printing - Gold, Karli (Biomaterials, 2018)
Most biomedical and pharmaceutical research of the human vascular system aims to unravel the complex mechanisms which drive disease progression from molecular to organ levels. The knowledge gained can then be used to innovate diagnostic and treatment strategies that can ultimately be determined precisely for patients. Despite major advancements, current modeling strategies are often limited at identifying, quantifying, and dissecting specific cellular and molecular targets that regulate human vascular diseases. Therefore, development of multiscale modeling approaches is needed that can advance our knowledge and facilitate the design of nextgeneration therapeutic approaches in vascular diseases. This article critically reviews animal models, static in vitro systems, and dynamic in vitro culture systems currently used to model vascular diseases. A leading emphasis on the potential of emerging approaches, specifically organ-on-a-chip and three-dimensional (3D) printing, to recapitulate the innate human vascular physiology and anatomy is described. The applications of these approaches and future outlook in designing and screening novel therapeutics is also presented.